Climate Variability, Drought, and Drought Management in Tunisia's Agricultural Sector - Verner, Dorte (World Bank, Washington, DC, 2018)
Climate change and recurrent climate events are making water-scarce countries like Tunisia and its agricultural lands drier and more vulnerable to drought. These recurrent climate events are also known as teleconnections and include natural climatic events such as the El Niño Southern oscillation (ENSO), the North Atlantic oscillation (NAO), and the Mediterranean oscillation (MO). These climate phenomena contribute to droughts, which negatively affect key rain-fed crops, suchas wheat and barley, and livestock. As a result, farmers are becoming more vulnerable as climate change and teleconnections make temperatures rise and rainfall become more sporadic. Agriculture is important for rural communities and the overall Tunisian economy. Twenty percent of the population is employed in agriculture, which accounts for 10 percent of the country’s gross domestic product (GDP) and 10 to 12 percent of total exports, on average. Wheat and other rainfedcrops are critical to food security and livestock survival and are the crops most affected by climate variability. Climate change’s adverse impacts on agriculture are a contingent liability for the Tunisian economy, including for the country’s GDP, trade balance, and balance of payments. As agricultural and agro-industrial outputs fall, food and fodder imports must rise to meet domestic demand. Therefore, this report suggests additional action on implementing integrated drought management (IDM) on top of what the government is already doing. Food and agriculture value chains are affected by climate events. This report includes detailed analyses of two key value chains, namely wheat and dairy. The analyses were done in representative lagging regions, including Jendouba for the dairy value chain and Siliana and Beja for the wheat value chain.Currently, wheat and dairy are the main subsectors in the lagging regions, and in the short term, strengthening these subsectors will increase jobs, incomes, and food security. This study finds that the El Niño Southern oscillation (ENSO) was a less important contributor to the 2015–16 drought in Tunisia than other teleconnections. ENSO drought impacts are more pronounced in other parts of the world than in the Middle East and North Africa (MENA) region. This report also examines wheat and dairy agriculture to determine how well they are adapting to climate change and climate variability. Current adaptation pathways to increase agricultural incomes and productivityfocus on increasing tree crops, which generally are more resilient to drought than field crops. Still, improving water management is also an essential part of this adaptation plan.